The burden of low back pain and its association with socio-demographic variables in the Middle East and North Africa region, 1990–2019 - Safiri, S; Nejadghaderi, SA; Noori, M; Sullman, MJM; Collins, GS; Kaufman, JS; Hill, CL; Kolahi, A-A (BioMed Central, 2023)
Background Low back pain (LBP) is the most common musculoskeletal disorder globally. Providing region- and national-specific information on the burden of low back pain is critical for local healthcare policy makers. The present study aimed to report, compare, and contextualize the prevalence, incidence and years lived with disability (YLDs) of low back pain in the Middle East and North Africa (MENA) region by age, sex and sociodemographic index (SDI), from 1990 to 2019.